GH Resistance Is a Component of Idiopathic Short Stature: Implications for rhGH Therapy - Savage, Martin O.; Storr, Helen L. (Frontiers in Endocrinology, 2021)
Idiopathic short stature (ISS) is a term used to describe a selection of short children for whom no precise aetiology has been identified. Molecular investigations have made notable discoveries in children with ISS, thus removing them from this category. However, many, if not the majority of children referred with short stature, are designated ISS. Our interest in defects of GH action, i.e. GH resistance, has led to a study of children with mild GH resistance, who we believe can be mis-categorised as ISS leading to potential inappropriate management. Approval of ISS by the FDA for hGH therapy has resulted in many short children receiving this treatment. The results are extremely variable. It is therefore important to correctly assess and investigate all ISS subjects in order to identify those with mild but unequivocal GH resistance, as in cases of PAPP-A2 deficiency. The correct identification of GH resistance defects will direct therapy towards rhIGF-I rather than hGH. This example illustrates the importance of recognition of GH resistance among the very large number patients referred with short stature who are labelled as ‘ISS’.